Study & Analysis of Intention of a BDI Agent and its Performance (International Journal of Engineering and Computer Science, 2015)
The reasoning ability is significant in an agent model and especially in BDI model. The belief, desire and intentions are the three important concepts in reasoning of the BDI agent. The response of a BDI agent is effective when the belief, desire and intention concepts are optimum. In this paper the efficiency of a BDI agent is analyzed by compelling the agent to dynamically revise the intention based on the perceptual input and achieve the target goal.